Accelerating Islamic Economy and Finance through Financial Technology: Challenges and Potential in the Digital Age - Supriadi, Iman; Maghfiroh, Rahma Ulva; Abadi, Rukhul (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2023)
The Islamic financial industry is increasingly experiencing rapid change and growth with technological advances, especially in the form of Financial Technology (FinTech). This research aims to analyze the regulatory challenges in the application of Financial Technology in the Islamic financial industry in Indonesia. This research uses a qualitative method with a literature study to collect and analyze data from various sources related to the application of FinTech in the Islamic financial industry and the associated regulatory challenges. The research findings show that several regulatory challenges need to be addressed in implementing FinTech in the Islamic finance industry in Indonesia. These challenges include Islamic perspectives on FinTech, efforts from government regulations and policies to encourage Islamic FinTech and the importance of collaboration between financial institutions and regulatory authorities. This research provides insight into the regulatory challenges faced in the implementation of FinTech in the Islamic finance industry in Indonesia. This research can guide the government, Islamic financial institutions, Islamic FinTech companies, and regulatory authorities in developing a regulatory framework conducive to the growth of Islamic FinTech.